Association between Plasma CEA Level and Tissue CEA Density with Clinical and Histopathological Features of Colorectal Cancer - Wismayer, Richard; Kiwanuka, Julius; Wabinga, Henry; Odida, Michael (Achievements and Challenges of Medicine and Medical Science Vol. 1, 2024)
Aim: The objectives of this study were to correlate elevations in plasma CEA levels with the extent of tissue CEA and determine the association of clinicopathological features with tissue CEA in primary tumours in Uganda. Introduction: Circulating levels of carcinoembryonic antigen (CEA) are widely accepted after primary tumour resection to monitor tumour recurrence and this marker has proved to be useful in the management of colorectal cancer. In Uganda and most parts of the world, carcinoembryonic antigen (CEA) is the most widely used tumour marker. This marker monitors tumour recurrence and is useful in the management of colorectal cancer (CRC). The aim of this study was to correlate elevations in plasma CEA levels with the extent of tissue CEA and determine the association of clinicopathological features with tissue CEA in Ugandan colorectal tumours. Preoperative elevation of CEA, and the degree of elevation, is associated with an increased risk of recurrence and decreased long-term survival. Methodology: A total of 119 patients with colorectal cancer specimens from September 2019 to September 2021 were recruited from four hospitals in central Uganda. A preoperative blood sample and the corresponding formalin fixed paraffin embedded tissue block were obtained from all participants. Data was abstracted from the clinical patients’ files on age, sex, stage, grade and topography of CRC. Haematoxylin and eosin sections were prepared to determine the histopathological subtype, grade, and lymphovascular invasion status. The plasma CEA levels were determined and the tissue CEA expression was detected using the indirect immunoperoxidase method which used monoclonal antibody CEA, DAKO Agilent USA< Clone I17 and reference IR622. Pearson chi-square test was used to assess the association between CEA expression and demographic and histopathological variables. Analysis of variance (ANOVA) was used to compare average plasma CEA levels (ng/ml) to tissue CEA intensities. Results: There were 31.4% CRC tissues in stage IV that stained positively for CEA compared to stage I (p=0.0101). Compared to 73.4% with grade II CRC which stained positively for CEA, there were 15.2% of CRC tissues with grade I that stained positively for CEA (p=0.0000). A positive correlation was found between the CRC tissue CEA and grade of CRC (r=+0.2204) and this reached statistical significance (p=0.0232). There was no relation between preoperative plasma CEA level and the CEA in the CRC tissue. Conclusions: This study showed a significant correlation between the grade of CRC and CRC CEA tissue expression. A higher incidence of lymph node metastasis is associated with a poorly differentiated CRC and a higher CRC tissue CEA expression. There was no correlation found between preoperative plasma CEA and tissue CEA. The study finding suggests a poorer prognosis for patients expressing high levels of CEA in their colorectal cancer tissue in Uganda.